Human Development of Small Scale Fishers: Evidence from Rana Pratap Sagar Reservoir Region, India - Khemraj Bunkar; Ananthan P.S.; Neha Wajahat Qureshi; Laxmi Lal Sharma; C. Sundaramoorthy (Journal of Indian Fisheries Association, 2022)
Fisheries is a sunrise sector in India with a huge untapped potential for fish production and employment generation. Of the vast and diverse inland aquatic resources, the reservoirs, spread over 3.15 million ha across the country, are considered a sleeping giant due to its unlocked potential for furthering fish production. Evidence suggests that fish stock enhancement programs in reservoirs have improved fish yield in many states. But as the studies on reservoir fisheries and the dependent fishers’ livelihoods are still limited, this work attempted to map the human development of fishers in the reservoir region of Rana Pratap Sagar (RPS) located on Chambal River valley in Rajasthan. Data was collected during 2020 and 2021, and analysed using MS Excel. Of the total fish catch (1806 tons), IMC accounted for 67%, followed by catfish (14%) and minor carps (11%). Occupational diversification was seen among the fishers as many of whom also worked as daily wage labourers. HDI was found to be very low (0:31) among the fishers, two third having less than <0.33, but also differed significantly depending upon where their settlement is or which sub-caste they belonged to or how much they earned from fishing. Importantly, fishers fared worst in terms of their education attainment (0.24) as compared to health (0.35) and standard of living (0.34) as compared to the general population. One important implication is that higher fish catch (or productivity) in the reservoir doesn’t directly translate into better human development status of dependent fishers, underscoring perhaps the role of governance and development support to ensure equity for marginalised small scale fishers in inland region.